Measurements and Analyses of 4G/5G Mobile Broadband Networks: An Overview and a Case Study. (14th April 2023) - El-Saleh, Ayman A.; Al Jahdhami, Majan Abdullah; Alhammadi, Abdulraqeb; Shamsan, Zaid Ahmed; Shayea, Ibraheem; Hassan, Wan Haslina
Abstract : Mobile data has become an integral part of everyday life, making Internet trends more and more profound and deeply embedded in life and the future. Mobile broadband (MBB) is one of the main aims of fifth-generation (5G) networks due to unprecedented growth in data demand. However, 5G networks are not yet deployed in many countries, whereas existing MBB networks, such as third generation (3G) and fourth generation (4G), are available in most world countries. As a result, there is a need to monitor and troubleshoot end-to-end network performance and ensure a better user experience. This paper provides an overview of MBB networks in terms of deployment environments, performance metrics, and implementation scenarios. It highlights the most important criteria for assessing MBB performance and the applications and measurement methods utilized, such as external and internal measurements and the classification of geographical areas. In addition, it provides measurement-based performance analyses of two existing mobile network operators (MNOs) (Omantel and Ooredoo) in the Sultanate of Oman. This performance analysis uses data measurements in various indoor and outdoor environments in five cities (Muscat, Ibra, Sur, Bahla, and Al kamil Wal Wafi). Several performance metrics are considered, such as signal level and quality, throughput, ping rate, and handover. Experimental results demonstrate that the 4G networks were the dominant networks in all measured locations for indoor and outdoor scenarios. Moreover, 5G data measurements are also recorded in the capital city of Oman, Muscat. The results of the 5G measurements show that both MNOs achieved a higher data rate with a lower ping rate.